Psikoedukasi “Strong Family, Smart Kids” Upaya Peningkatan Pengetahuan Serta Identifikasi Perkembangan Kognitif Anak Usia Dini - Wahyu Putri; Djudiyah; ⁠Siti Fasikhah (Penerbit Jurnal Indonesia, 2026)
Parents' understanding of child development knowledge will be very helpful in parenting. This study aims to develop knowledge and identify children's cognitive development for parents of Kindergarten X Malang City because many parents still do not understand the importance of early stimulation and their role as the main companion in their child's growth and development. The method in this study used a pre-experimental model with a one-group pretest–posttest design, and applied a child's cognitive development measurement scale and the